1996
DOI: 10.1093/jn/126.3.728
|View full text |Cite
|
Sign up to set email alerts
|

The Expressed Protein in Glyphosate-Tolerant Soybean, 5-Enolypyruvylshikimate-3-Phosphate Synthase from Agrobacterium sp. Strain CP4, Is Rapidly Digested In Vitro and Is not Toxic to Acutely Gavaged Mice

Abstract: The safety of 5-enolpyruvylshikimate-3-phosphate synthase enzyme derived from Agrobacterium sp. strain CP4 (CP4 EPSPS) was assessed. CP4 EPSPS is the only protein introduced by genetic manipulation that is expressed in glyphosate-tolerant soybeans, which are being developed to provide new weed-control options for farmers. Expression of this protein in plants imparts high levels of glyphosate tolerance. The safety of CP4 EPSPS was ascertained by evaluating both physical and functional characteristics. CP4 EPSPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
100
0
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(109 citation statements)
references
References 26 publications
7
100
0
2
Order By: Relevance
“…This dose is at least 1,300 times greater than the dose that might potentially be taken by man, which would only be obtained if CP4 EPSPS were also expressed in maize, tomatoes and potatoes, and without considering the degradation of the protein before human consumption. No acute adverse effect was observed in the animals treated (Harrison et al 1996). Thus, the studies carried out to evaluate the administering of appreciable quantities of the protein CP4 EPSPS or of Roundup Ready® soybeans have demonstrated that there is no acute or chronic toxic effect detectable.…”
Section: Toxicologymentioning
confidence: 93%
See 2 more Smart Citations
“…This dose is at least 1,300 times greater than the dose that might potentially be taken by man, which would only be obtained if CP4 EPSPS were also expressed in maize, tomatoes and potatoes, and without considering the degradation of the protein before human consumption. No acute adverse effect was observed in the animals treated (Harrison et al 1996). Thus, the studies carried out to evaluate the administering of appreciable quantities of the protein CP4 EPSPS or of Roundup Ready® soybeans have demonstrated that there is no acute or chronic toxic effect detectable.…”
Section: Toxicologymentioning
confidence: 93%
“…For the bacteria, we selected the protein of Escherichia coli K12 and three deposited sequences corresponding to Agrobacterium tumefaciens. Two of these corresponded to genes identifi ed in the two genome projects accomplished and the third sequence was deposited following work done by Harrison et al (1996), with the transformation of soybeans that gave rise to Roundup Ready® soybeans. Table I illustrates the results obtained from aligning the EPSPS proteins sequenced in different organisms.…”
Section: The Gene Aro a And The Protein Epspsmentioning
confidence: 99%
See 1 more Smart Citation
“…Monsanto has published the research results that were submitted to FDA on the composition of glyphosate tolerant soybeans, toxicity, and feeding studies in a series of peer-reviewed articles in the Journal of Nutrition (Hammond, et al;Harrison, et al;Padgette, et al 1996b). In addition, research results on the composition of glyphosatetolerant soybeans treated with glyphosate, which were not originally submitted to FDA, were published in the Journal of Agriculture and Food Chemistry (Taylor, et al).…”
Section: Intended Effectsmentioning
confidence: 99%
“…The processes for obtaining plants that are resistant or tolerant to glyphosate are discussed by Shaner and Bridges (2002) and Meilan et al (2002), and are nearly always based on the super-expression of the gene responsible for producing the EPSPS enzyme or on the use of amino acid sequences that cause a greater affinity of the enzyme with PEP, which binds to shikimate when producing EPSPS (as, for example, in the configuration that corresponds to the CP4 EPSPS Agrobacterium gene presented by Harrison et al, 1996). In soybean cultivars resistant to the herbicide, both modifications are present.…”
Section: Introductionmentioning
confidence: 99%